STUDY OF DECREASING TEMPERATURE OF YTTRIUM-IRON-GARNET (YIG) SINTERING PROCESS WITH THE ADDITION OF CETYL TRIMETHYL AMMONIUM BROMIDE (CTAB) ADITIVE: COMPREHENSIVE REVIEW - Anjasmoro, Danu
The development of wold telecommunicatios has reached the fifth generation (5G) due to the world’s need for a faster internet to support new technology in the 4.0 industrial revolution based on the internet of things (IOT). This raises the need to optimization of microwave transmission at high frequencies. Cicrculator is one of the important elements used in microwave transmission has been done for a lot of research, especially on the type of ferrite to produce lowest insertion loss and highest insulation. This literature study is expected to be taken into consideration in optimization of YIG fabrication through solid-state process. The study was conducted by collecting data from various sources to provide information about the Yttrium-Iron-Garnet (YIG) and Yttrium-Iron-Perovskite (YIP) phases. This information contains the characteristics of each phase and the influence of the presence of the YIP phase on the YIG application. In addition, data collection was also carried out regarding the effect of adding CTAB (Cetyl Trimethyl Ammonium Bromide) and YIG fabrication process parameters on the presence of the YIP phase, microstructure, and density values. The changes that occur due to differences in the fabrication process will change the magnetic characteristics and response of microwaves. All of this information is presented in tabular form. Then, an analysis of the positive, negative impacts and prospects of future research is carried out. From the results of literature studies indicate that the presence of the YIP phase and the degree of densification that occurs will affect the magnetic characteristics and microwave response. In order to obtain high density YIG, optimization is required at each stage of the process and the use of CTAB at the mixing stage. The use of CTAB will prevent the agglomeration process so that YIG synthesis occurs at a lower sintering temperature and showed no effect on the magnetic characteristics of YIG. YIG doped Gd applications can produce an insertion loss value at a frequency of 4.2 GHz of 0.24 dB. This value can still be reduced by decreasing the magnetization value which regulates the composition and type of doping and increasing the YIG density value through the selection of raw materials in the form of YIP and Fe2O3, the mixing process parameters and the optimal sintering process.